Enteric nervous system in microbiota-associated gut inflammation - Yang, Cen; Lan, Xuping; Zhong, Huijie; Geng, Jiawei; Wang, Wenxue (Frontiers in Immunology, 2026)
The enteric nervous system (ENS), a distinctive and intricate compartment of the peripheral nervous system (PNS), is characterized by its capacity to autonomously coordinate fundamental gut functions independent of central nervous system (CNS) input. Comprising vast, densely packed networks of neurons and glial cells distributed throughout the intestinal wall, the ENS not only directly governs motility, secretion, and absorption but also engages in dynamic crosstalk with intestinal immune cells to establish immune defense barriers and fine-tune inflammatory responses. This system is persistently exposed to and deeply engaged with a dynamic microenvironment shaped by both external (e.g., microbiota and their metabolites) and internal (e.g., immune cells, stromal cells) signals. The gut microbiota and its metabolic products play pivotal roles in maintaining mucosal barrier integrity and orchestrating the progression of intestinal inflammation. They influence the development and repair of enteric neurons and can directly participate in disease pathogenesis or exert their effects through immune-mediated mechanisms. This review delves into the complex interplay between the ENS and the gut microbiota within the context of intestinal inflammation pathogenesis.